Overexpression of the ribosome-inactivating protein OsRIP1 modulates the jasmonate signaling pathway in rice - Chen, Simin; De Zutter, Noémie; Meijer, Anikó; Gistelinck, Koen; Wytynck, Pieter; Verbeke, Isabel; Osterne, Vinicius J. S.; Kondeti, Subramanyam; De Meyer, Tim; Audenaert, Kris; Van Damme, Els J. M. (Frontiers in Plant Science, 2024)
Ribosome-inactivating proteins (RIPs) are plant enzymes that target the rRNA. The cytoplasmic RIP, called OsRIP1, plays a crucial role in regulating jasmonate, a key plant hormone.Understanding the role of OsRIP1 can provide insights into enhancing stress tolerance and optimizing growth of rice. Transcription profiling by mRNA sequencing was employed to measure the changes in gene expression in rice plants in response to MeJA treatment. Compared to wild type (WT) plants, OsRIP1 overexpressing rice plants showed a lower increase in mRNA transcripts for genes related to jasmonate responses when exposed to MeJA treatment for 3 h. After 24 h of MeJA exposure, the mRNA transcripts associated with the gibberellin pathway occurred in lower levels in OsRIP1 overexpressing plants compared to WT plants. We hypothesize that the mechanism underlying OsRIP1 antagonization of MeJA-induced shoot growth inhibition involves cytokininmediated leaf senescence and positive regulation of cell cycle processes, probably via OsRIP1 interaction with 40S ribosomal protein S5 and α-tubulin. Moreover, the photosystem II 10kDa polypeptide was identified to favorably bind to OsRIP1, and its involvement may be attributed to the reduction of photosynthesis in OsRIP1-overexpressing plants subjected to MeJA at the early timepoint (3 h).